Cisplatin Nephrotoxicity and Longitudinal Growth in Children With Solid Tumors. Issue 34 (August 2015) - Jiménez-Triana, Clímaco Andres; Castelán-Martínez, Osvaldo D.; Rivas-Ruiz, Rodolfo; Jiménez-Méndez, Ricardo; Medina, Aurora; Clark, Patricia; Rassekh, Rod; Castañeda-Hernández, Gilberto; Carleton, Bruce; Medeiros, Mara; Frank, Liu.
<x xml:space="preserve">Abstract</x> Abstract Cisplatin, a major antineoplastic drug used in the treatment of solid tumors, is a known nephrotoxin. This retrospective cohort study evaluated the prevalence and severity of cisplatin nephrotoxicity in 54 children and its impact on height and weight. We recorded the weight, height, serum creatinine, and electrolytes in each cisplatin cycle and after 12 months of treatment. Nephrotoxicity was graded as follows: normal renal function (Grade 0); asymptomatic electrolyte disorders, including an increase in serum creatinine, up to 1.5 times baseline value (Grade 1); need for electrolyte supplementation <3 months and/or increase in serum creatinine 1.5 to 1.9 times from baseline (Grade 2); increase in serum creatinine 2 to 2.9 times from baseline or need for electrolyte supplementation for more than 3 months after treatment completion (Grade 3); and increase in serum creatinine ≥3 times from baseline or renal replacement therapy (Grade 4). Nephrotoxicity was observed in 41 subjects (75.9%). Grade 1 nephrotoxicity was observed in 18 patients (33.3%), Grade 2 in 5 patients (9.2%), and Grade 3 in 18 patients (33.3%). None had Grade 4 nephrotoxicity. Nephrotoxicity patients were younger and received higher cisplatin dose, they also had impairment in longitudinal growth manifested as statistically significant worsening on the height Z Score at 12 months after treatment. We used a multiple logistic regression model using the delta of height Z Score (baseline-12 months) as dependent variable in order to adjust for the main confounder variables such as: germ cell tumor, cisplatin total dose, serum magnesium levels at 12 months, gender, and nephrotoxicity grade. Patients with nephrotoxicity Grade 1 where at higher risk of not growing (OR 5.1, 95% CI 1.07–24.3, P = 0.04). The cisplatin total dose had a significant negative relationship with magnesium levels at 12 months (Spearman r = −0.527, P = <0.001).